Hubungan Pengetahuan Dan Sikap Ibu Hamil Tentang Faktor 4t (Terlalu Tua, Terlalu Muda, Terlalu Banyak Dan Terlalu Dekat) Dengan Risiko Komplikasi Kehamilan di Puskesmas Tj. Unggat - Lince Nainggolan; Umi Eliawati; Elvi Murniasih (STIKes Ibnu Sina Ajibarang, 2025)
Deviations from normal that directly cause pain and death for the mother and baby. The high maternal mortality rate is caused by high risk, namely women with 4T conditions (pregnancies that occur at too young an age, too old an age, too close a pregnancy distance, too many children). This study aims to determine the relationship between knowledge and attitudes of pregnant women about the 4T factors with pregnancy complications in the Tanjung Unggat Community Health Center working area. The research design used in this research is cross sectional analysis. The sampling technique in this research was accidental sampling of 38 people. The results of research conducted on 38 respondents conducted in August 2024 showed that 22 respondents had sufficient knowledge with a p value of 0.002, where there was a relationship between knowledge and high risk pregnancy (4T) at the Tanjung Unggat Health Center. Meanwhile, there were 25 respondents who had a positive attitude and the risk of pregnancy complications with a p value of 0.000, where there was a relationship between attitude and high risk pregnancy (4T) at the Tanjung Unggat Community Health Center. It is hoped that respondents will better understand the concept of high risk of 4T during pregnancy and be more concerned about the mother's health when planning the next pregnancy.